Outcomes of three Euratom projects on cogeneration of electricity, heat and hydrogen - Serin Canet; Glückler Martin; Pasquet Michel; Vaglio-Gaudard Claire (EPJ Nuclear Sciences & Technologies)
This paper deals with the assessment of low-carbon energy generation solutions (heat, electricity, hydrogen) provided by nuclear reactors in the general framework of nuclear co-generation addressed by three ongoing Euratom projects, GEMINI 4.0, NPHyCo and TANDEM. It gives a short overview over the three projects, points out the respective objectives and methodologies and describes the current results. Focus is given to the common outcomes of all three projects. The main common outcomes are that low-carbon hydrogen production via nuclear energy is generally feasible and can be done safely. This is easier to be achieved with new-build plants (Small Modular Reactors and High Temperature Reactors) than with existing nuclear power plants in operation. With current price of carbon dioxide certificates and the existing hydrogen infrastructure, low-carbon hydrogen production is not economically competitive compared to hydrogen from fossil sources. Thus, governmental support (national and EU-wide) is needed to foster low-carbon hydrogen production as a means to real decarbonization goals.